Caracterização do perfil comportamental e de competência social de indivíduos com a síndrome del22q11.2 - Costa, Gabriela Mello; Ganthous, Giulia; Santos, Amanda Oliveira; Giacheti, Célia Maria (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
Abstract:PURPOSE:to characterize the behavioral problems and social competence of individuals with del22q11.2 syndrome and compare them with typically developing individuals, according to information from parents.METHODS:participated in this study 24 parents of individuals of both sexes between 6 and 18 years, being 12 individuals with the syndrome del22q11.2 (sample group) and 12 individuals with typically developing (control group). The behavioral inventory Child Behavior Checklist (CBCL) was applied.RESULTS:eight of the twelve patients with the syndrome were classified as clinical as the scales of behavior and Internalizing Problems. Five of the twelve individuals of sample group were clinical as the scales of behavior and Externalizing Problems. The skills of social competence, ten of the twelve individuals sample group were clinical.CONCLUSION:individuals with the diagnostic of the del22q11.2 syndrome, according with opinion their parents present behavioral and social problems in different degrees of commitment. Comparing the groups, was observed statistically significant differences in variables of externalizing and internalizing behaviors. Therefore, we conclude that the sample group presents more abnormal behavior compared to the control group.

Resumo:OBJETIVO:caracterizar os problemas comportamentais e de competência social de indivíduos com a síndrome del22q11.2 e compará-los com indivíduos com desenvolvimento típico, segundo informação dos pais.MÉTODOS:participaram desta pesquisa 24 pais de indivíduos de ambos os gêneros, entre seis e 18 anos, sendo 12 indivíduos com a síndrome del22q11.2 (grupo amostral) e 12 indivíduos com desenvolvimento típico (grupo controle). Foi aplicado o inventário comportamental Child Behavior Checklist (CBCL).RESULTADOS:oito dos 12 indivíduos com a síndrome foram classificados como clínico nas escalas de comportamento e Problemas Internalizantes; cinco dos 12 indivíduos do grupo amostral foram classificados como clínico quanto às escalas de comportamento e Problemas Externalizantes. Nas habilidades de competência social, dez dos 12 indivíduos do grupo amostral foram classificados como clínico.CONCLUSÃO:indivíduos com diagnóstico da síndrome del22q11.2 apresentaram, segundo opinião dos pais, problemas comportamentais e de competência social, em diferentes graus de comprometimento. Quando realizada a comparação entre os grupos pode-se observar diferenças estatisticamente significantes em variáveis dos comportamentos externalizantes e dos comportamentos internalizantes. Desta forma, concluí-se que o grupo amostral apresenta comportamentos mais alterados quando comparados ao grupo controle.
Characterization of behavior profile and social competence of individuals with the del22q11.2 syndrome
Keywords: Speech, Language and Hearing Sciences; Behavior; Interpersonal Relations; Communication; Social Behavior Disorders; DiGeorge Syndrome; Fonoaudiologia; Comportamento; Relações Interpessoais; Comunicação; Transtornos do Comportamento Social; Síndrome de DiGeorge